Phylogenetic affinities of the enigmatic Bare‐faced Bulbul Pycnonotus hualon with description of a new genus. (6th April 2018) - Fuchs, Jérôme; Pasquet, Eric; Stuart, Bryan L.; Woxvold, Iain A.; Duckworth, J. W.; Bowie, Rauri C. K.
Abstract : The recently described Bare‐faced Bulbul Pycnonotus hualon from Lao PDR has a very distinct morphology and habitat (karsts). Mitochondrial and nuclear data from the type material demonstrated that P. hualon is sister to members of the genus Spizixos . To highlight its unique morphology and phylogenetic distinctiveness, we describe a new monotypic genus for the Bare‐faced Bulbul.